Pengembangan Sistem Informasi Pemesanan dan Reservasi Berbasis Web pada Kafe Teras House - Caca Arif Herdian; Maya Destriani; Tazkia Salsabila Ardan; Zaini Dahlan; Iqbal Rizki Maulana; Raihan Saputra (Global, 2026)
Teras House faced operational constraints due to conventional transaction and reservation systems, such as overlapping table schedules and slow financial recapitulation. This study aimed to develop a fully integrated web based menu ordering and table reservation information system. The novelty of this system lay in its adaptation to the unique characteristics of a third-place business model that combined culinary activities and room facility management. The methodology employed was the system development life cycle, which encompassed requirement analysis, object-oriented modeling, interface design, coding, and functional testing. The results indicated that the system integration successfully resolved operational bottlenecks and automated revenue recapitulation. Through black-box testing conducted on nineteen functional requirement specification items, all features were declared successful and valid without any system failures.